The Price of Euro: Evidence from Sovereign Debt Markets - Erik Makela (Aboa Centre for Economics (ACE), 2014)
The objective of this paper is to figure out how the Economic and Monetary Union in Europe (EMU) has affected on its member's sovereign risk-premiums and long-term government bond yields. In order to estimate the effect, this paper utilizes synthetic control method. Contrary to the popular belief, this paper finds that the majority of member countries did not receive economic gains from EMU in sovereign debt markets. Synthetic counterfactual analysis finds strong evidence that Austria, Belgium, France, Germany and Netherlands have paid positive and substantial euro-premium in their 10-year government bonds since the adoption of single currency. After the latest financial crisis, government bond yields have been higher in all member countries compared to the situation that would have been without monetary unification. This paper concludes that from the sovereign borrowing viewpoint, it would be beneficial for a country to maintain its own currency and monetary policy.
Keywords: F34; E42; G15; 330; Synthetic Control Method; Monetary Union; Sovereign Risk; Government Bond Yield